ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KAKAO (Theobroma cacao L) DI KECAMATAN PANTE BIDARI KABUPATEN ACEH TIMUR - Desi Amalia; Muslimah Muslimah; Siti Balqies Indra (MEDIAGRO, 2020)
ABSTRACT The direction of this study was to determine the level of income and feasibility of cocoa farming in Pante Bidari District, East Aceh Regency. In this study respondents were determined based on the type of maintenance of cocoa plantations, namely untreated gardens, poorly maintained gardens, intensive care gardens and gardens that practice IPM based on the knowledge they have gained from the Office and NGOs. The data used in this study are primary data obtained from sample farmers, and secondary data obtained from the Department of Agriculture and related parties. Based on the results of this study, the results show that cocoa farms that are cared for and not cared for are able to generate income to farmers, whereas when analyzed using a comparison between costs and income, the results show that only gardens that are intensively treated that is 1,07 and 1,18. Keyword: Cocoa, Feasibility, Maintenance, Productivity, Revenue.